Grandmothers: Central scaffolding sources impacting maternal and infant feeding practices in Colombia - Natalia Concha; Sandra Jovchelovitch (Wiley, 2021)
Abstract A growing body of evidence highlights that maternal and child nutrition programmes need to extend beyond the mother-child dyad by adopting a family systems approach, particularly in the Global South. Guided by a sociocultural and community psychology understanding of health, the paper explores factors identifying grandmothers as central resources for nutrition programmes. The study was conducted in a Colombian urban periphery applying a qualitative longitudinal design (prenatal and postpartum). It is based on interviews with adolescent mothers and mothers in their 20s (n = 35 at T1; n = 21 at T2), grandmothers (n = 15 at T1; n = 12 at T2) and community/public stakeholders (n = 17). Many of the participants live in low‐income households headed by grandmothers, who adjust feeding practices to the extent of their economic capacity. Findings reveal grandmothers play a central role in decision‐making and in enabling a holistic support system for the dyad. This is defined as grandmothers' scaffolding; it covers nutrition advice, breastfeeding and infant feeding, cultural practices, caregiving and maternal mental health. The study helps build the evidence‐base for the transferability of a family systems approach to Global South regions by using sociocultural and community psychology concepts to fortify the rationale for including grandmothers in maternal and child nutrition programmes. It argues for the need to continue raising the visibility of key actors like grandmothers and for nutrition programmes to align themselves more flexibly with the needs of families experiencing poverty.